Intermodal beat frequency stability in a polarization stabilized HeNe laser with an optical switch - Budzyń, Grzegorz; Podżorny, Tomasz; Rzepka, Janusz (Photonics Letters of Poland, 2014)
We investigated the behaviour of a frequency stabilized 1mW two mode helium-neon laser incorporating an optical switch. In the paper we compare the stability of the intermodal frequency when the error signal is taken either from main or the parasite output of the tube. The possibility of using the constructed laser in the non-interferometric optical measurement device working with precision in the range of 1ppm is given. Full Text: PDF References K. Seta, T. O’Ishi, "Distance meter utilizing the intermode beat of a He–Ne laser", App. Opt. 29(3), 354 (1990). CrossRef T. Araki, S. Yokoyama, N. Suzuki, "Simple optical distance meter using an intermode-beat modulation of a He-Ne laser and an electrical-heterodyne technique", Rev. Sci. Instr. 65(6), 1883 (1994). CrossRef J. Rzepka, J. Pieńkowski, H. Pawołka, S. Sambor, "Two-frequency laser interferometer with phase shift measurement", Opt. App. XXVII(4), (1997). S. Yokoyama, T. Araki N. Suzuki, "Intermode beat stabilized laser with frequency pulling", App. Opt. 30(3), 358 (1994). CrossRef Wysocki G., Abramski K.M., "Frequency stabilisation of twin orthogonal mode He-Ne laser", Opt. App., vol. XXXII, no. 1-2, pp. 207-213, (2002) DirectLink Rzepka J., Maltese P., "Frequency stabilization of Zeeman He-Ne laser using a surface-stabilized ferroelectric liquid crystal", Proc SPIE, vol. 3186, pp. 162-166, 1997 CrossRef Wang. L., et al., "Laser Frequency Stabilization Based on Control of Intermode Beat Note", Chinese Journal of Lasers 34 (9) , pp. 1198-1202, 2007 DirectLink Kim M.-S., Kim S.-W., "Two-Longitudinal-Mode He-Ne Laser for Heterodyne Interferometers to Measure Displacement", App. Opt. 41(28), 5938, 2002 CrossRef Budzyń G., "Optokomutacyjna stabilizacja lasera dwumodowego", PhD Thesis, Wrocław University of Technology, Wrocław, 2006 Anishenko M. L., et al, "Natural Intensity and Intermode Beating Frequency Fluctuations in Two-Mode He-Ne and He-Ne/CH4 Lasers", Las. Phys., Vol. 1, No. 5, pp. 511-534, 1991 DirectLink Lindberg A., "Mode frequency pulling in He–Ne lasers", Am. J. Phys. 67 (4), pp. 350-353 CrossRef T. Yoshino, "Reflection Anisotropy of 6328 A Laser Mirrors", Japn. J of App. Phys., vol. 18, no. 8, pp. 1503-1507 CrossRef Podżorny T., Budzyń, G., Rzepka, J., ICMEM 2012 (2012), pp. 137-140 J.Y. Yeom and T.H. Yoon, "Three-longitudinal-mode He-Ne laser frequency stabilized at 633 nm by thermal phase locking of the secondary beat frequency", App. Opt. 44, 266-270 (2005) CrossRef